Penilaian Prestasi Kerja Karyawan PTPN III Pematangsiantar Dengan Metode Simple Additive Weighting (SAW) - Agus Perdana Windarto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2017)
Performance appraisal of employees is absolutely done to know the achievements that have been achieved every employee. With achievement appraisal means subordinates get attention from the topics to encourage their passionate work, with reference to the process of honest and objective assessment and there follow-up. Follow-up appraisals enable employees to be promoted, demotivated, cultivated, and rewarded for service. The purpose of this study is to make a decision support system employee performance appraisal employee used to increase the class. This decision support system uses Simple Additive Weighting (SAW) Method. Where the criteria used are Work Attitude Employees, How Employees Work, Employees Work and Employee Duty Day. The sample data used is 5 with different weights on each criterion. This study took a case study of PTPN III Pematangsiantar with the calculation that 0.90 has the highest value according to SAW calculation. The value is in the name of Mr. Syamsul Arifin, SE. Therefore this method can be used to assess employees by entering actual data in the system created and can solve the selection problem in multi-process decision making.